Play at the center of the curriculum - Van Hoorn, Judith; Nourot, Patricia Monighan ;Scales, Barbara;Alward Keith Rodriguez (Upper Saddle River, New Jersey : Pearson, 2015)
Interweaves anecdotes of children$1 (Bs play, theories of play and development, empirical evidence from research, and practical instructional strategies to give students a clear look at play and the curriculum.s
1. Looking at play through teacher's eyes -- 2. Play and development : theory -- 3. Play as the cornerstone of development: the literature -- 4. Orchestrating children's play: setting the stage -- 5. Orchestrating play: interactions with children -- 6. Play as a tool for assessment -- 7. Mathematics in the play-centered curriculum -- 8.Language, literacy and play -- 9. Science in the play-centered curriculum -- 10. The arts in the play-centered curriculum -- 11. Play and socialization -- 12. Outdoor play -- 13. Toys and technology as tools for play -- 14. Conclusion: integrating play, development, and practice.
Includes bibliographical references and index.
Keywords: PLAY